Description on the prevalence of Proteus mirabilis through an integrated sampling framework for health, food, and environment in Northeast India and an integrative review with reference to one health context - Chowdhury, Goutam; Majumdar, Tapan; Modi, Dilem; Dolma, Karma G.; Chaliha Hazarika, Suranjana; Sarmah, Pallab; Das, Samaresh; Mukhopadhyay, Asish K.; Ojha, Anup Kumar; Das, Madhuchhanda; Ramamurthy, Thandavarayan (Frontiers in Microbiology, 2026)
IntroductionFoodborne infections caused by different pathogens are a perennial public health problem in India. An uncommon enteric pathogen Proteus mirabilis has been frequently isolated from the hospitalized diarrheal cases and different food and environmental samples collected from four states in Northeast India. This study was aimed at characterizing P. mirabilis isolates to show its etiological importance in public health and also present a review indicating its global prevalence of antimicrobial resistance and detection virulence genes reported from different sources.MethodsIn this study, we have screened 6,298 diarrheal stools from hospitalized patients, 12,305 market foods, 4,270 state-specific foods, and 2,130 environmental samples. P. mirabilis was isolated and identified by routine microbiological methods. Representative isolates were examined for antimicrobial susceptibility, putative virulence-encoding genes by PCR, and whole-genome sequencing (WGS) analysis.ResultsThough the isolation rate of P. mirabilis was low in diarrheal cases (0.4%), its prevalence was detected mostly in environmental samples (3.2%). All the P. mirabilis isolates from diarrheal stools showed resistance to doxycycline, erythromycin, and tetracycline. The majority of the P. mirabilis isolates from market foods were resistant to nalidixic acid (92.6%), erythromycin (81.5%), tetracycline, and doxycycline (77.8% each). Isolates from state-specific foods showed higher resistance to quinolone/fluroquinolones, erythromycin, tetracycline, and doxycycline. Meropenem resistance has also been recorded in isolates from market foods and state-specific foods (7.4% and 37.5%, respectively). Of the 15 P. mirabilis isolates tested in the PCR assay, the majority of them were positive for pmfA and eight other virulence genes.DiscussionAlthough these genes are responsible for urinary tract infections (UTIs), some of them are known to induce diarrhea in vivo. WGS analysis has identified SPI-1 for the first time in P. mirabilis, with other virulence genes associated with diarrhea. Considering its presence in several sources, strengthening the One Health approach is important to implement strategies in order to control P. mirabilis-mediated infections.